Exchange-rate risk and exports: evidence from a set of transition economies - Hasanov, Akram Shavkatovich; Baharumshah, Ahmad Zubaidi (Taylor & Francis, 2014)
This article investigates the hypothesis that exchange-rate risk may have an effect on exports for a set of transition countries, namely, Belarus, Kazakhstan, Russia, and Ukraine. To assess this effect, although a two-step estimation approach has earned an extensive empirical record in the literature, a number of studies in this context do not appear to support this approach due to a potential generated regressor issue. This dissonance in a two-step estimation procedure seems to have been somewhat resolved by a relatively new branch of empirical approach that exploits a multivariate version of generalized autoregressive conditional heteroskedasticity in-mean models. The findings suggest that the effect of exchange-rate risk seems to be detrimental in Belarus and Ukraine. However, for Russia and Kazakhstan, which are heavily dependent on crude oil exports, the effect has been found to be indeterminate.